Pedagogical Content Knowledge Practices of Public School Science Teachers - Cordova, Williza; Linaugo, Joji (Technium Social Sciences Journal, 2022)
Abstract. Pedagogical Content Knowledge (PCK) is used to determine the development of pedagogical and disciplinary science teachers; knowledge over time. Hence, investigating the extent of PCK practice is essential as it predicts how teachers carry out instructions. The study determined science teachers’ extent of PCK practice in public schools in a medium-sized division in Central Philippines in the areas of Subject Matter Knowledge (SMK), Instructional Representation Strategies (IRS), Instructional Objective and Context (IOC), and Knowledge of Students’ Understanding (KSU) using the descriptive-comparative research design. Using a researcher-modified questionnaire, the study was conducted to 208 respondents who were identified through stratified random sampling. The findings revealed that the extent of PCK practice is very great. A significant difference exists in the extent of PCK practice in terms of SMK and IOC when teachers are grouped according to age, grade level taught, and length of teaching service. Likewise, there is a significant difference in the extent of PCK practice in terms of KSU when respondents are grouped according to the grade level taught. This means that although female doctorate degree elementary teachers with longer teaching experience perform better, all science teachers, have a very great subject matter mastery, effective instructional delivery, context and objectives, and processing and evaluation of students’ knowledge.